1999
DOI: 10.1063/1.369401
|View full text |Cite
|
Sign up to set email alerts
|

Strong enhancement of optical absorbance from ionic self-assembled multilayer thin films of nanocluster Pt and polymer dye

Abstract: The observation of unusually enhanced optical absorbance spectra of ionic self assembled multilayer (ISAM) thin films composed of alternating layers of Pt nanoclusters (<1 nm dimension) and polymer dye is reported. The first bilayer absorbance is found to be considerably larger than that of several succeeding bilayers even though there is no difference in composition for each bilayer. A layer-by-layer-dependent redshift in maximum wavelength position due to the strong coupling of metals and polymer mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The rough surface of nanostructured metals can induce large scattering of photons and increase the absorption in semiconductor [24] as observed in the present case. The obtained results clearly highlight the importance of the presence of W modifier over the surface of BTO thin film for increasing the absorption of UV photons for both PD-2 and PD-3 photodetectors.…”
Section: Optical Studiesmentioning
confidence: 80%
“…The rough surface of nanostructured metals can induce large scattering of photons and increase the absorption in semiconductor [24] as observed in the present case. The obtained results clearly highlight the importance of the presence of W modifier over the surface of BTO thin film for increasing the absorption of UV photons for both PD-2 and PD-3 photodetectors.…”
Section: Optical Studiesmentioning
confidence: 80%
“…The bilayers provide the individual dye molecules with direct contact to gold nanoparticles, giving a greatly increased absorbance owing to surfaceenhancement phenomena. 3 The absorption enhancement is due to a charge-transfer mechanism where by electronic excitation may be transferred between the dye molecule and the metallic nanocluster. As more bilayers are built, a slight redshift in maximum absorbance is observed, indicating a greater number of charge transfers through the ionic bands of the dye molecules and gold nanoclusters.…”
Section: Resultsmentioning
confidence: 99%
“…2 Further studies indicated that such films show an enhancement of optical absorption at specific wavelengths owing to a strong resonance interaction between the metallic nanoparticles and the dye molecules. 3 Widely different electrodeposition techniques have been used to construct oligothiophenelinked metallic nanoparticles by use of organic bridging molecules. 4,5 Additionally, polystyrene spheres have been used as templates for metallic nanoparticle adsorption, making it possible to tune the optical properties of a film by controlling particle sizes and densities.…”
Section: Introductionmentioning
confidence: 99%
“…The optical fiber sensor system operates based on a variation of the modal domain concept discussed in prior publications [6][7][8][9][10][11]. By exposing the optical fiber to the flowing multiphase field, and performing required signal processing on the output two-dimensional speckle interference signal, measurements that allow discrimination of multiple flowing material phases and their flow rates may be determined.…”
Section: Figure 2 Field Preparation Of Logging Toolmentioning
confidence: 99%